Are patients with polycystic ovary syndrome more prone to irritable bowel syndrome?. Issue 4 (26th April 2022) - Kałużna, Małgorzata; Kompf, Pola; Wachowiak-Ochmańska, Katarzyna; Moczko, Jerzy; Królczyk, Aleksandra; Janicki, Adam; Szapel, Karol; Grzymisławski, Marian; Ruchała, Marek; Ziemnicka, Katarzyna
Abstract : Background: Polycystic ovary syndrome (PCOS) encompasses endocrine, reproductive and metabolic disturbances. Abdominal pain and bowel movement disturbances are common complaints of PCOS patients. It remains uncertain whether the characteristic features of PCOS are associated with an increased incidence of irritable bowel syndrome (IBS). Methods: In the study, 133 patients with PCOS diagnosed according to international evidence - based guidelines and 72 age- and BMI-matched eumenorrheic controls were enrolled. Anthropometric measurements and biochemical and hormonal characteristics were collected. The Rome IV criteria were used for IBS diagnosis. Quality of life (QoL) and depressive symptoms were also assessed. Results: IBS symptom prevalence in PCOS was not significantly different than in controls. Hyperandrogenism and simple and visceral obesity did not appear to affect IBS prevalence in PCOS. There were no anthropometric, hormonal or biochemical differences between IBS-PCOS and non-IBS-PCOS patients, apart from IBS-PCOS patients being slightly older and having lower thyroid-stimulating hormone. Metabolic syndrome (MS) prevalence was higher in IBS-PCOS than non-IBS-PCOS. QoL appears to be significantly lower in IBS-PCOS compared to PCOS-only patients. The occurrence of depression was higher in IBS-PCOS vs non-IBS-PCOS patients. At least one alarm symptom was reported by 87.5% of IBS-PCOS; overall, this group experienced more alarm symptoms than the IBS-only group. Conclusions: Since a link between PCOS and IBS comorbidity and increased MS prevalence was noted, patients presenting with both conditions may benefit from early MS diagnostics and management. The high incidence of alarm symptoms in PCOS women in this study highlights the need for differential diagnosis of organic diseases that could mimic IBS symptoms.